2007
DOI: 10.1063/1.2751502
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of neutral and singly charged keV atomic particles with gas-phase adenine molecules

Abstract: KeV atomic particles traversing biological matter are subject to charge exchange and screening effects which dynamically change this particle's effective charge. The understanding of the collision cascade along the track thus requires a detailed knowledge of the interaction dynamics of radiobiologically relevant molecules, such as DNA building blocks or water, not only with ionic but also with neutral species. We have studied collisions of keV H(+), He(+), and C(+) ions and H(0), He(0), and C(0) atoms with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 27 publications
0
33
0
Order By: Relevance
“…Effectively, important damage induced by the interaction of ionizing radiation with biological tissues is due to the secondary particles, low-energy electrons, radicals, or singly and multiply charged ions generated along the track after irradiation of the biological medium [10]. Experimental and theoretical studies have thus been developed on collisions between ions and molecular or even biomolecular targets [5][6][7][8][9][11][12][13][14] in order to understand the different mechanisms involved at the molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…Effectively, important damage induced by the interaction of ionizing radiation with biological tissues is due to the secondary particles, low-energy electrons, radicals, or singly and multiply charged ions generated along the track after irradiation of the biological medium [10]. Experimental and theoretical studies have thus been developed on collisions between ions and molecular or even biomolecular targets [5][6][7][8][9][11][12][13][14] in order to understand the different mechanisms involved at the molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…Kim at al. [24] also observed evidence for metastable dissociation of pure and hydrated adenine cluster ions, while Alvarado et al [49] have shown that adenine cation fragmentation can proceed via CN loss followed by neutral H loss after a microsecond-order delay. Modelling ion flight times demonstrated that either A + or AH + formation by A 2 + dissociation in the drift tube could produce the observed feature.…”
Section: Comparing Mpi and Eii Of Hydrated Adenine Complexesmentioning
confidence: 99%
“…E.g., for collision of alpha particles with amino acids [15] or carbon ions with thymine [16], kinetic energies in the order of 5 eV were found and the energy was increasing with the charge state of the carbon projectile. While charge transfer plays an important role in ionization by carbon ions [17], it was experimentally found to have little impact for the ionization by protons [18]. Recent theoretical work quantifies that the charge transfer cross section for pyrimidine nucleobases in collisions of C 4+ is four orders of magnitude higher than in collisions with protons (controversially, it would be lower in the case of deoxyribose) [19].…”
Section: Ion Detectionmentioning
confidence: 99%
“…For pyrimidine, it was discussed that the energy transferred to some deeper molecular orbitals decreases with the electron energy while it increases for protons, that have their cross section maximum at lower energies (at about 100 keV) [34]. Charge transfer would lead to even stronger fragmentation for multiple charged cation projectiles [16], but for singly charged ions, especially for protons, the charge transfer cross section is low [18,35].…”
Section: The Parent C 4 H 8 Omentioning
confidence: 99%